Incentive System Design in Creativity-Dependent Firms - Grabner, Isabella (The Accounting Review, 2014)
ABSTRACT I empirically investigate the impact of an organization's creativity dependency on the design of its incentive system. In firms for which the primary source of value creation is the creativity of core employees, the designs of incentive systems are particularly challenging. The nature of creative work constrains the feasibility of extrinsic incentives, but at the same time creates a need for them. Accordingly, there is concern that the use of incentives renders people not creative enough, but a lack of incentives makes employees “too creative.” I argue that a solution to this dilemma is the acknowledgment that the decision to use performance-based pay is not made in isolation, but as part of a set of complementary choices. I theoretically argue and empirically show that subjective evaluations of non-task-related performance and performance-based pay are complements in a creativity-dependent setting. I further argue that the intense use of both control mechanisms is the incentive system that best accommodates the control requirements of creativity-dependent firms, and show that the likelihood of choosing this system increases with the creativity dependency.